FISCAL POLICY AND NATIONAL SAVINGS IN THE CZECH REPUBLIC AND SLOVAKIA - Musil, Petr; Vincencová, Eva (Journal of Advanced Studies in Finance; Vol 3 No 1 (2012): JASF Volume III Issue 1(5) Summer 2012, 2012)
The goal of the paper is to analyse the influence of fiscal policy on the national savings in the Czech Republic and Slovakia. In other words, the authors are about to compare the theory of Barro Ricardian equivalence in the conditions of the Czech and Slovak economy. Firstly, the authors introduce the theory of Barro Ricardian equivalence and secondly, they show the relevant data of the key economic variables (such as national savings, household savings and government savings). Due to the specific conditions that must be fulfilled in order to pronounce the B-R theory valid the authors set the following hypothesis: the B-R equivalence neither in the Czech Republic nor in Slovakia was ever being valid.